2007
DOI: 10.1007/s10765-007-0232-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties of Rare-Earth-Stabilized Zirconia and Zirconate Pyrochlores as Surrogates for Actinide-Doped Zirconia

Abstract: Thermophysical properties of rare-earth-stabilized zirconia and zirconate pyrochlores, A 2 Zr 2 O 7 (A = La, Nd, Sm, Gd, Dy, Y), were evaluated by X-ray diffractometry, Raman spectroscopy, and the ultrasound pulse-echo method. Crystallographic analyses elucidated that had the pyrochlore structure, whereas Dy 2 Zr 2 O 7 and Y 2 Zr 2 O 7 had the defect fluorite structure. For lanthanide pyrochlores, the thermal expansion became smaller with increasing ionic radius of A and increasing crystal binding energy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
68
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 21 publications
16
68
0
3
Order By: Relevance
“…Shimamura et al reported that the lattice parameters of Ln2Zr2O7 pyrochlores increased with the ionic radius of Ln, as shown in Fig. 2 [18]. The lattice parameter of LZ is 10.8 Å in Shimamura's experiments and 10.802 Å in Tabira's work [21].…”
Section: Crystal Structurementioning
confidence: 86%
See 4 more Smart Citations
“…Shimamura et al reported that the lattice parameters of Ln2Zr2O7 pyrochlores increased with the ionic radius of Ln, as shown in Fig. 2 [18]. The lattice parameter of LZ is 10.8 Å in Shimamura's experiments and 10.802 Å in Tabira's work [21].…”
Section: Crystal Structurementioning
confidence: 86%
“…Two peaks, (331) and (511), shown in the LZ pattern originate from pyrochlore structure, and are also observed in Nd2Zr2O7, Sm2Zr2O7, and Gd2Zr2O7 patterns. Other peaks are commonly observed for the pyrochlore and defect fluorite structures [18]. Ln2Zr2O7 pyrochlore crystal is a cubic structure in space group 3 (origin choice 2) with four crystallographically independent atom sites (rear earth ion Ln, in 16d at ( , , ) , Zr in 16c at (0,0,0), O1 in 48f at (x, , ) and O2 in 8b at ( , , ).…”
Section: Crystal Structurementioning
confidence: 94%
See 3 more Smart Citations